Biocontrol Of Fusarium Wilt Of Vanilla (Vanilla Planifolia) Using Combined Inoculation Of Trichoderma Sp. And Pseudomonas Sp. - ATHUL SANDHEEP R.,; AJU K. ASOK ANS JISHA M.S, (International Journal of Pharma and Bio Sciences, 2012)
Fungal pathogens pose a major problem in causing reduction in yield of vanilla crop to considerable level. Fusarium oxysporum, was isolated from naturally infected vanilla plants and an attempt was made to minimize the damage caused by the pathogen using biocontrol agents Trichoderma harzianum, and Pseudomonas fluorescens isolated from soil. The combined inoculation of Trichoderma harzianum with Pseudomonas fluorescens treatment showed maximum disease suppression followed by the single inoculation of Pseudomonas fluorescens, Trichoderma harzianum, Pseudomonas putida, Trichoderma virens, respectively in decreasing order. The results clearly indicated that these bio-control agents suppress the disease incidence. Concerning the interaction effect between used antagonistic microorganisms and method of treatments, there was a highly significant effect. These results suggested that using of Trichoderma harzianum with Pseudomonas fluorescens through soil mixing plus root dipping treatment could be provided not only additional protection against crop loss due to Fusarium diseases but also significantly increased vegetative growth of vanilla. The mechanism of biocontrol involved the production of volatile and non volatile organic acids, siderophore, chitinase, peroxidise and salicylic acid. Application of biocontrol agents for crop protection is very significant as it has several advantages such as possibility of multiple pathogen suppression, low cost and promotion of soil fertility.